Proceedings of the 21st International Conference on Information Integration and Web-Based Applications &Amp; Services 2019
DOI: 10.1145/3366030.3366064
|View full text |Cite
|
Sign up to set email alerts
|

URL-based Phishing Detection using the Entropy of Non-Alphanumeric Characters

Abstract: Cyber phishing is a theft of personal information in which phishers, also known as attackers, lure users to surrender sensitive data such as credentials, credit card and bank account information, financial details, and other behavioral data. The ones who commit such crimes are called 'Phishers' or 'Attackers.' Phishers act as if they are reliable sources to lure users to gain access/control to their system. Phishing detection is becoming a crucial research area, attracting increased focus as the number of phis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The survey pointed out that support vector machine (SVM) and lexical features are the most widely used machine learning algorithm and type of features respectively. Many studies, such as [7][8][9][10], focus on detecting only phishing malicious web pages since vast majority of the malicious links in internet created for phishing purposes [11]. In this context, [7] and [8] used lexicalbased URL features only to identify malicious links, while [12] extended the feature extraction with JavaScript client code analysis to achieve a better detection rate.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey pointed out that support vector machine (SVM) and lexical features are the most widely used machine learning algorithm and type of features respectively. Many studies, such as [7][8][9][10], focus on detecting only phishing malicious web pages since vast majority of the malicious links in internet created for phishing purposes [11]. In this context, [7] and [8] used lexicalbased URL features only to identify malicious links, while [12] extended the feature extraction with JavaScript client code analysis to achieve a better detection rate.…”
Section: Related Workmentioning
confidence: 99%
“…The authors reviewed 13 studies between 2014 and 2019 in terms of algorithms used, performance metrics and proc and cons in the study. Same authors made another survey [9] on the datasets used by researchers about malicious input for feature extraction and training of models [9]. The analysis showed that most studies use imbalanced datasets as the number of phishing sites cannot be compared with that of legitimate URLs.…”
Section: Related Workmentioning
confidence: 99%